Axial compression behaviour of rectangular recycled aggregate concrete-filled steel tubular stub columns - Yang, Dongdong; Liu, Faqi; Wang, Yuyin (Journal of constructional steel research, 2023)
Recycled aggregate concrete-filled steel tubular (RACFST) column is a type of composite column that combines the mechanical efficiencies of concrete-filled steel tubular (CFST) columns and the economic and environmental advantages of recycled aggregate concrete (RAC). Till now, experimental and numerical investigations on the axial compressive behaviour of rectangular RACFST columns are not sufficient and design methods for axial compressive stiffness, peak strain and steel tube local stability are still lacking. This study presents experiments on 16 rectangular RACFST stub columns subject to axial compression, investigating the effects of replacement ratio of recycled coarse aggregate (RCA), aspect ratio and depth to thickness ratio of steel tube. The full-range axial load vs. deformation behaviour, working mechanism and failure mode of rectangular RACFST columns are found to be similar to those of natural CFST counterparts, while the occurrence of the first local buckling of steel tube is advanced due to the incorporation of RCA. The increase in replacement ratio negatively affects the axial stiffness of rectangular RACFST columns more than the load-bearing capacity. Nonlinear finite element analysis is subsequentially conducted, and the influences of replacement ratio and aspect ratio on the axial compressive performance and confinement effect of rectangular RACFST columns are numerically studied. On the basis of extensive test data and parametric studies, practical recommendations are finally given for designing the ultimate capacity, axial compressive stiffness, peak strain and tube local buckling of rectangular RACFST stub columns. •16 rectangular RACFST stub columns were tested under axial compression.•FEA modelling on axial behaviour of rectangular RACFST columns was carried out.•Effects of replacement ratio and aspect ratio on the axial performance were studied.•Design recommendations for strength, deformation and local stability were given.